2020
DOI: 10.2174/0929867326666190227230024
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs: Potential Novel Prognostic and Diagnostic Biomarkers in Colorectal Cancer

Abstract: Background: Long non-coding RNAs (lncRNAs), a type of regulatory RNAs, play a key role in numerous cellular pathways. Ectopic expression of this group of non-coding RNAs has been specified to be involved in numerous diseases. Moreover, the role of lncRNAs in the initiation and development of cancers including colorectal cancer (CRC) has been acknowledged. Objective: In the present review, the role of lncRNAs as prognostic and diagnostic biomarkers in CRC as well as the molecular mechanisms of their contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…Long non‐coding RNAs (lncRNAs) are well‐established mediators that play critical roles in various cellular pathways 6 . It is reported that X‐inactivation‐specific transcript (XIST) is a lncRNA as an indicator of many human tumours 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs) are well‐established mediators that play critical roles in various cellular pathways 6 . It is reported that X‐inactivation‐specific transcript (XIST) is a lncRNA as an indicator of many human tumours 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the mode and regulatory mechanism of lncRNAs in tumors have not been thoroughly studied, lncRNAs are verified to play a vital role in the occurrence and development of human cancers [ 5 ]. At present, it has been found that related lncRNAs are involved in the occurrence, metastasis and invasion, early diagnosis, prognosis evaluation, and radiotherapy and chemotherapy efficacy of CRC [ 6 , 7 ]. LncNEAT1 was reported to promote CRC progression by suppressing miR-486-5p expression and regulating NR4A1/Wnt/ β -catenin pathway [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs affect critical CRC signaling pathways by acting both as oncogenes and tumor suppressors through interactions with other regulatory molecules (13)(14)(15). Several lncRNAs have been reported to be dysregulated in CRC, suggesting promising potentiality for theranostic applications (16)(17)(18). However, the molecular mechanisms of action in CRC pathobiology were elucidated only for few of them, such as, CCAT1, CCAT2, H19, HOTAIR, MALAT1, and UCA1 (19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%